The Effect of Tax Planning, Deferred Tax Expense, and Profitability on Profit Management - Grandis, Reza Oktaviana; Nursiam, Nursiam (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2024)
This research was carried out to know and analyze the influence of tax planning, deferred tax burden, and profitability on earnings management in manufacturing companies listed on the BEI in 2020-2022. The data used in this research are financial reports on manufacturing companies listed on the Stock Exchange (BEI) in the 2020-2022 period. The sampling method uses a purposive sampling method, namely based on the suitability of characteristics. Based on this method, 156 samples were obtained that met the criteria from 74 companies. Hypothesis testing in this research uses classical assumption tests and multiple linear regression analysis using the SPSS 25 application. The results of the research show that tax planning and profitability affect earnings management, while deferred tax expenses do not affect company earnings management.